Scientific Interpretation and Its Significance in the Development of Science - Mesi Rawanita; Syabuddin Syabuddin (Seutia Hukamaa Cendekia, 2024)
Scientific interpretation is an approach to the interpretation of the Qur'an that utilizes modern scientific knowledge as an instrument to understand verses related to natural phenomena and natural laws. This article explores the role of scientific interpretation in bridging religious texts with science and its contribution to the development of science itself. The method used is a literature review and critical analysis of the relevance of Qur'anic verses to modern science. The results of the study show that scientific interpretation has the potential to expand the scientific horizons of Muslims and facilitate constructive dialogue between religion and science. In addition, this approach can significantly contribute to understanding the complexity of the relationship between religious texts and contemporary scientific discoveries. Nevertheless, the study also highlights the methodological and interpretive challenges faced in applying scientific interpretation, including the risk of subjectivity and bias in understanding the text. Therefore, a careful, systematic, and principle-based approach is needed to maximize the benefits of scientific interpretation. This article concludes that scientific interpretation has excellent potential to be an effective tool in developing science while strengthening the understanding of Islam that is relevant to the context of the times.